Parents increase their parental effort when aided by helpers in a cooperatively breeding bird. - Valencia-Ruíz, Juliána; de la Cruz, Carlos; Carranza, Juan; Mateos, Concha (Elsevier, 2006)
In cooperatively breeding species, parents may be assisted by other individuals to feed the young. How breeding parents react when they receive help is poorly understood. Evidence suggests that parents usually maintain their feeding effort when starvation of chicks is common, and reduce it when other risks such as predation are more important for chick survival, although some recent examples do not fit this pattern. In no case, however, have parents been found to increase their effort when they have helpers. We investigated this issue in a rarely studied cooperative breeder, the azure-winged magpie, Cyanopica cyanus. Breeders increased their provisioning rate when aided by helpers. However, chick starvation was rare and it was equally so in nests with and without helpers. The incidence of predation, conversely, was significantly lower in the presence of helpers. Helpers provisioned at a lower rate than parents but buffered the effect of adverse conditions in bad years in the nests they assisted. To our knowledge, these findings show for the first time that parents can increase their investment in the current brood in the presence of helpers, a result that does not seem to have been covered by current theory of cooperative breeding.
https://v2.sherpa.ac.uk/id/publication/10562
Keywords: Aves - Reproducción; Aves - Conducta social; Cooperative breeding; Parental effort; Helping behaviour